Patterns and drivers of biodiversity–stability relationships under climate extremes. (28th November 2017) - De Boeck, Hans J.; Bloor, Juliette M. G.; Kreyling, Juergen; Ransijn, Johannes C. G.; Nijs, Ivan; Jentsch, Anke; Zeiter, Michaela
Abstract: Interactions between biodiversity loss and climate change present significant challenges for research, policy and management of ecosystems. Evidence suggests that high species diversity tends to increase plant community stability under interannual climate fluctuations and mild dry and wet events, but the overall pattern of diversity–stability relationships under climate extremes is unclear. We comprehensively review results from observational and experimental studies to assess the importance of diversity effects for ecosystem function under climate extremes. Both the broad literature review and a meta‐analysis focused on the effects of extreme precipitation events on above‐ground biomass reveal no significant interaction between species richness and climate extremes. Causes for variation in diversity effects under climate extremes are explored, from stress thresholds to biotic interactions and community assembly, and we consider how these may modulate the outcomes of biodiversity–stability relationships. We also examine how specific characteristics of climate extremes and timing of measurements may interact with mechanisms of diversity–stability relationships. Synthesis . Hypotheses tailored to the complexity of diversity effects, the implementation of standardised experiments and the use of trait‐based biodiversity measures rather than species richness should lead to better causal understanding of whether and how biodiversity may protect ecosystems from adverse effects of climate extremes. Abstract : We comprehensively review results from observational and experimental studies to assess the importance of biodiversity effects for ecosystem function under climate extremes and find no significant interaction between species richness and extremes. Causes for the observed variation in effects are explored, and suggestions are made to improve causal understanding of whether and how biodiversity may protect ecosystems from adverse climate extreme effects.